Momentum, heat, and neutral mass transport in convective atmospheric pressure plasma-liquid systems and implications for aqueous targets. (23rd September 2015) - Lindsay, Alexander; Anderson, Carly; Slikboer, Elmar; Shannon, Steven; Graves, David
Abstract: There is a growing interest in the study of plasma-liquid interactions with application to biomedicine, chemical disinfection, agriculture, and other fields. This work models the momentum, heat, and neutral species mass transfer between gas and aqueous phases in the context of a streamer discharge; the qualitative conclusions are generally applicable to plasma-liquid systems. The problem domain is discretized using the finite element method. The most interesting and relevant model result for application purposes is the steep gradients in reactive species at the interface. At the center of where the reactive gas stream impinges on the water surface, the aqueous concentrations of OH and ONOOH decrease by roughly 9 and 4 orders of magnitude respectively within 50 m of the interface. Recognizing the limited penetration of reactive plasma species into the aqueous phase is critical to discussions about the therapeutic mechanisms for direct plasma treatment of biological solutions. Other interesting results from this study include the presence of a 10 K temperature drop in the gas boundary layer adjacent to the interface that arises from convective cooling. Though the temperature magnitudes may vary among atmospheric discharge types (different amounts of plasma-gas heating), this relative difference between gas and liquid bulk temperatures is expected to be present for any system in which convection is significant. Accounting for the resulting difference between gas and liquid bulk temperatures has a significant impact on reaction kinetics; factor of two changes in terminal aqueous species concentrations like H2 O2, NO, and NO are observed in this study if the effect of evaporative cooling is not included.